2014
DOI: 10.1089/bfm.2014.0113
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Out on Safe Sleep: Evidence-Based Infant Sleep Recommendations

Abstract: The American Academy of Pediatrics (AAP) issued recommendations in 2005 and 2011 to reduce sleep-related infant death, which advise against all bedsharing for sleep. These recommendations overemphasize the risks of bedsharing, and this overemphasis has serious unintended consequences. It may result in increased deaths on sofas as tired parents try to avoid feeding their infants in bed. Current evidence shows that other risks are far more potent, such as smoking, shared sleep on sofas, sleeping next to impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…17 Sleeping with an infant on surfaces such as sofas, chairs or recliners, further increases the risk of SIDS associated with bed sharing and many infant deaths related to bed sharing are likely due to situations of accidental sleeping, when parents had not planned to bedshare. 12,17,20 Kendall-Tackett et al found that up to 25% of a sample of primarily breastfeeding mothers fell asleep with their infants in unsafe sleep locations, such as chairs, sofas or recliners. 20 We cannot directly address this issue, since we did not specifically ask mothers about instances of inadvertently falling asleep in various locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Sleeping with an infant on surfaces such as sofas, chairs or recliners, further increases the risk of SIDS associated with bed sharing and many infant deaths related to bed sharing are likely due to situations of accidental sleeping, when parents had not planned to bedshare. 12,17,20 Kendall-Tackett et al found that up to 25% of a sample of primarily breastfeeding mothers fell asleep with their infants in unsafe sleep locations, such as chairs, sofas or recliners. 20 We cannot directly address this issue, since we did not specifically ask mothers about instances of inadvertently falling asleep in various locations.…”
Section: Discussionmentioning
confidence: 99%
“…819 Parents may receive conflicting advice, resulting in confusion and possibly the adoption of even riskier behaviors, such as unplanned sleeping with infants on sofas, chairs or recliners. 8,13,17,20 …”
Section: Introductionmentioning
confidence: 99%
“…191 In recent years, the concern among public health officials about bed-sharing has increased, because there have been increased reports of SUIDs occurring in highrisk sleep environments, particularly bed-sharing and/or sleeping on a couch or armchair. 196 -198 On the other hand, some breastfeeding advocacy groups encourage safer bedsharing to promote breastfeeding, 199 and debate continues as to the safety of this sleep arrangement for low-risk, breastfed infants. In an analysis from 2 case-control studies in England (1993-1996 and 2003-2006), Blair et al 200 reported an adjusted OR of bed-sharing (excluding bed-sharing on a sofa) for infants in the absence of parental alcohol or tobacco use of 1.1 (95% CI: 0.6-2.9).…”
Section: Figurementioning
confidence: 99%
“…They conclude that ''the only evidence-based universal advice is that sofas are hazardous places for adults to sleep with infants, that exposure to smoke, both prenatal and postnatal, increases the risk of death, and that sleeping next to an impaired caregiver increases the risk of death.'' 1 As members of the AAP Task Force on SIDS, we respectfully disagree on several points. The authors list several ''leading'' risk factors for SIDS and accidental suffocation (e.g., smoking, prone sleeping, formula feeding, infant sleeping unattended, poverty, sofa sleeping, and parental use of alcohol/drugs).…”
mentioning
confidence: 97%